2008
DOI: 10.1017/s0958344008000633
|View full text |Cite
|
Sign up to set email alerts
|

The potential of using a mobile phone to access the Internet for learning EFL listening skills within a Korean context

Abstract: Interest in the use of a mobile phone to access the Internet for learning English in general, and listening skills in particular, has been increasing in Korea over the last few years. However, there has been only a small number of studies on this topic in Korea. The present paper investigates the potential of using a mobile phone to browse wireless application protocol (WAP) sites for the purpose of learning listening skills. The study focuses specifically on the attitudes of language learners toward using a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 28 publications
4
67
0
8
Order By: Relevance
“…Before 2010, much of the research includes Palm devices, mobile phones and other hand-held devices such as the iPod. Most of these studies can be narrowed to several topics, including the following: SMS messaging to teach vocabulary [3], [6], [21], [17], [1]; general vocabulary instruction [4], [9]; pronunciation [3]; listening skills [18]; student usage [8] and student perceptions [11], [8].…”
Section: A Mobile Learning In the Second Language Classroommentioning
confidence: 99%
See 1 more Smart Citation
“…Before 2010, much of the research includes Palm devices, mobile phones and other hand-held devices such as the iPod. Most of these studies can be narrowed to several topics, including the following: SMS messaging to teach vocabulary [3], [6], [21], [17], [1]; general vocabulary instruction [4], [9]; pronunciation [3]; listening skills [18]; student usage [8] and student perceptions [11], [8].…”
Section: A Mobile Learning In the Second Language Classroommentioning
confidence: 99%
“…The author found that there were several advantages to using mobile learning for vocabulary instruction, such as: it is more effective than using flashcards, it is ubiquitous [15], [18], it provides instant feedback; information can be located instantly via the Internet and there are increased interactions between the teacher and the student and the student and the student.…”
Section: A Mobile Learning In the Second Language Classroommentioning
confidence: 99%
“…Various studies have pointed out the challenges and disadvantages of MALL that result from the limitations of mobile technology (e.g., Nah, White, & Sussex, 2008;Thornton & Houser, 2003) and the high cost of mobile devices (e.g., Kiernan & Aizawa, 2004;Stockwell, 2008), yet a decade of MALL implementation has shown that these tools can provide language learners with real-world opportunities to negotiate meaning and to engage with comprehensible input and output by optimizing e-mail, MALL software, short message service (SMS), online discussion boards, and class management systems. However, little research has been conducted regarding the target tasks that language learners themselves feel they need or want to do using the four target language skills (listening, speaking, reading, and writing) in language learning classrooms that incorporate MALL.…”
Section: Moonyoung Park and Tammy Slater In Response To The Research Prmentioning
confidence: 99%
“…The researchers, hence, believed that mobile learning is a fruitful instructive tool in learning language skills in general and vocabulary items in particular. Nah et al (2008) studied the effectiveness of mobile learning in developing listening skills among EFL Korean undergraduate students. This has been carried out by investigating the students' attitudes towards using smart phones in listening activities, either individually or within a group.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Beyond no doubt, acquiring a foreign or a second language attracts the interest of educationalist worldwide (Kukulska-Hulme, 2009;Cavus & Ibrahim, 2009;Al-Ansari, 2006). For example, acquiring lexical items, and developing listening skills in Korea (Nah et al, 2008) are crucial when learning a foreign or a second language. Therefore, educationalist find it necessary to employ mobile learning in their classrooms.…”
Section: Introductionmentioning
confidence: 99%